Methionine suppresses autophagy in Cryptococcus neoformans: Impact of GPP2 gene deletion on the expression of autophagy-related genes - Padilla, Adrián Adolfo Álvarez; Martho, Kevin Felipe Cruz; Felizardo, Gabrielle; Pascon, Renata Castiglioni; Vallim, Marcelo Afonso (Folia microbiologica, 2026)
Autophagy is an essential intracellular degradation and recycling system for macromolecules and organelles, crucial for cell survival under nutrient stress conditions. In fungi, the genes involved in vesicle assembly during autophagy have been extensively characterized. However, in the pathogen Cryptococcus neoformans, the autophagy pathway remains less understood, particularly regarding its potential connections with virulence and pathogenicity. Our previous work identified Gpp2 as a key player in the biosynthesis of the sulfur-containing amino acid methionine. Through transcriptomic analysis, we observed that through transcriptomic analysis, we observed that deletion of GPP2 in C. neoformans leads to the repression of several core autophagy genes (ATG1, ATG2, ATG4, ATG15, VPS15, and VPS30), likely as an indirect consequence of altered methionine metabolism, while upregulating PEP4 expression. Since methionine is known to repress autophagy in Saccharomyces cerevisiae, we hypothesized that this amino acid might similarly regulate autophagy in C. neoformans. Our experiments demonstrated that both endogenous and exogenous methionine inhibit the expression of autophagy-related genes not only in the wild-type H99 strain but also in gpp2Δ and gpr4Δ mutant strains. Intriguingly, we found that GPR4 deletion creates a mutant unable to sense exogenous methionine, consequently releasing the repression of autophagy genes. Furthermore, microscopic analyses revealed that methionine supplementation substantially reduces autophagosome formation compared to methionine-deprived conditions. These results lead us to conclude that methionine biosynthesis regulation in gpp2Δ strains affects autophagy similarly to S. cerevisiae; GPR4 encodes a functional methionine receptor in C. neoformans; and methionine availability directly impacts autophagic flux, where the methionine receptor Gpr4 links extracellular amino acid availability to the intracellular control of autophagy likely via the Cys3/Gpp2 regulatory axis. This work provides crucial insights into the metabolic regulation of autophagy in pathogenic fungi and opens new avenues for understanding fungal pathogenesis mechanisms.
Keywords: Methionine; Amino acid uptake; Autophagy; GPR4; PMSF